Modality selective roles of pro-nociceptive spinal 5-HT2A and 5-HT3 receptors in normal and neuropathic states. (December 2018) - Patel, Ryan; Dickenson, Anthony H.
Abstract: Descending brainstem control of spinal nociceptive processing permits a dynamic and adaptive modulation of ascending sensory information. Chronic pain states are frequently associated with enhanced descending excitatory drive mediated predominantly through serotonergic neurones in the rostral ventromedial medulla. In this study, we examine the roles of spinal 5-HT2A and 5-HT3 receptors in modulating ascending sensory output in normal and neuropathic states. In vivo electrophysiology was performed in anaesthetised spinal nerve ligated (SNL) and sham-operated rats to record from wide dynamic range neurones in the ventral posterolateral thalamus. In sham rats, block of spinal 5-HT3 Rs with ondansetron revealed tonic facilitation of noxious punctate mechanical stimulation, whereas blocking 5-HT2A Rs with ketanserin had minimal effect on neuronal responses to evoked stimuli. The inhibitory profiles of both drugs were altered in SNL rats; ondansetron additionally inhibited neuronal responses to lower intensity punctate mechanical stimuli and noxious heat evoked responses, whereas ketanserin inhibited innocuous and noxious evaporative cooling evoked responses. Neither drug had any effect on dynamic brush evoked responses nor on spontaneous firing rates in both sham and SNL rats. These data identify novel modality and intensity selective facilitatory roles of spinal 5-HT2A and 5-HT3 receptors on sensory neuronal processing within the spinothalamic-somatosensory cortical pathway. Graphical abstract: Highlights: Spinal 5-HT3 Rs facilitate noxious mechanical sensory transmission in sham rats. Spinal 5-HT2A R block reveals minimal tonic activity in sham rats. Enhanced descending facilitation of evoked but not spontaneous neuronal activity in SNL rats. Cold and heat transmission facilitated via spinal 5-HT2A and 5-HT3 Rs respectively in SNL rats.